La difícil recuperación cultural de un espacio que ha sido olvidado a través de la historia y en un intento de recuperación, a simple vista se ve cinta adhesiva (2021)
Our personal interest for this paper is drawn from our common and natural interest as students of  rchitecture for asking about the state of monuments of heritage interest, historical sites in which history passes, and many times their traces are erased, but however it remains something appreciable, at first glance. The park el Bosque de la Republican was one of the most attended and beautiful parks of all Colombia, located in Tunja in the center of the city, it is a park that has suffered the abandonment by different mandates, a park built with all the love of the world in homage to the centenary of the martyrs killed in the name of freedom by the Spanish crown, a park to which a diversity of birds did not long ago, but which made the space pleasant, a park with different types of trees , materiality, expression, but what about this park that for many citizens and visitors that affected them emotionally at one time was important? What is their status? How has your journey been throughout history?